MORPHOMETRY AND HISTOLOGY STRUCTURE OF CEREBELLUM OF BALI DUCKS - Sekar Aurellya Savira; Ni Luh Eka Setiasih; Luh Gde Sri Surya Heryani (Buletin Veteriner Udayana, 2025)
The cerebellum, located in the dorsal region of the medulla oblongata and pons, is the largest component of the hindbrain. It plays a crucial role in motor coordination, nerve control, and maintaining body balance. This study aimed to analyze the anatomical and histological structure, as well as the morphometry, of the cerebellum in male and female growing-phase Bali ducks. A total of 20 Bali ducks (10 males and 10 females, aged 3 months each) were used in this study. The cerebellum was extracted for anatomical observation and weight measurement. Subsequently, the samples were processed into histological preparations using Hematoxylin-Eosin (HE) staining to examine the histological structure and morphometric parameters. Anatomically, the cerebellum was positioned at the posterior region of the head, beneath the temporal and occipital lobes and above the brainstem. The average cerebellar weight was 0.6 grams in males and 0.5 grams in females. Histologically, the cerebellar structure was consistent across both sexes, comprising gray matter (molecular layer, granular layer, and Purkinje/ganglionar layer) and white matter. Morphometric analysis revealed the following mean layer thicknesses in males: molecular layer (156.29 ± 17.72 µm), granular layer (69.73 ± 11.26 µm), Purkinje layer (6.44 ± 1.68 µm), and white matter (50.11 ± 19.16 µm). In females, the corresponding values were 145.47 ± 15.07 µm, 66.83 ± 11.37 µm, 6.83 ± 1.64 µm, and 52.89 ± 18.56 µm, respectively. Statistical analysis indicated no significant differences (P > 0.05) in cerebellar weight or layer thickness between male and female Bali ducks. Further research with a larger sample size and additional parameters, such as biochemical or functional studies, could provide deeper insights into sex-related variations in cerebellar characteristics.